PURCHASING STRATEGIES IN THE KRALJIC PORTFOLIO MATRIX – A CASE STUDY IN OPEN PIT COAL MINING - Alim Perdana; Nur Budi Mulyono (PERHAPI, 2021)
Kraljic matrix (or Kraljic model) is a method used to segment the purchases or suppliers of a company by dividing them into four quadrants, based on the complexity (or risk) of the supply market (such as monopoly situations, barriers to entry, technological innovation) and the importance of the purchases or suppliers (determined by the impact that they have on the profitability of the company). This quandrant allows the company to define the optimal purchasing strategies for each of the four types of purchases or suppliers. In coal mining company, hundred thousand goods, part number or SKUs are purchased by corporate in fulfilling its mining operations requirement. However, the commodities generally purchased by open pit coal mining company are classified into 6 (six) classes which are fuel, maintenance of mobile equipment, blasting material, tyre, lubricants, and others. With the complexity of dealing with suppliers, it is mandatory for developing purchasing strategies as part of managing of supply chain. Mining operations and profitability of coal mining company shall depend on the total cost of ownership in purchasing the abovementioned commodities. This Kraljic Portfolio Model (1983) will assist coal mining company in applying purchasing strategies based on the class or quadrant which has been developed. Objective of this research is to develop purchasing strategies by empirically quantifying using data from a comprehensive survey among purchasing professionals in coal mining industry. Kraljic Portfolio Matrix is developed with 2 (two) stages of questioner. First questioner is to assess the importance level of each attribute in the dimension of purchasing activity by using Analytical Hierarchy Process. Second questioner is to assess every commodity’s scoring against each supply attribute. Subsequently, the matrix is developed by using SPSS (Statistical Product and Service Solutions) software. This research successfully classifies purchasing commodity in the appropriate quadrant of Kraljic Portfolio Matrix. By classifying the commodities purchased by coal mining company in the right quadrant of Kraljic Portfolio Matrix, the company will be able to implement the right purchasing strategies which will be different in one quadrant and another.